People's Attitudes, Beliefs, and Experiences Regarding Polypharmacy and Willingness to Deprescribe. Issue 9 (26th August 2013) - Reeve, Emily; Wiese, Michael D.; Hendrix, Ivanka; Roberts, Michael S.; Shakib, Sepehr
<x xml:space="preserve">Abstract</x> Objectives To capture people's attitudes, beliefs, and experiences regarding the number of medications they are taking and their feelings about stopping medications. Design Administration of a validated questionnaire. Setting Multidisciplinary ambulatory consulting service at the Royal Adelaide Hospital. Participants Participants were individuals aged 18 and older (median 71.5) taking at least one regular prescription medication; 100 participants completed all items of the questionnaire, 65 of whom were aged 65 and older. Measurements Participants were administered the 15‐item Patients' Attitudes Towards Deprescribing (PATD) questionnaire. Results Participants were taking an average of 10 different prescription and nonprescription (including complementary), regular and as‐needed medications. More than 60% felt that they were taking a "large number" of medications, and 92% stated that they would be willing to stop one or more of their current medications if possible. Number of regular medications, age, and number of medical conditions were not found to be correlated with willingness to stop a medication. The findings were similar in older and younger participants. Conclusion This study has shown that a cohort of mostly older adults were largely accepting of a trial of cessation of medication(s) that their prescriber deemed to be no longer required. Because few factors were associated with willingness to cease medications, all patients should be individually evaluated for deprescribing.